Institutional Differentiation and Educational Politics in Indonesian Islamic Educational Institutions - Muhammad Ainur Rohim; Moh. Ayyub Musthofa; Masdar Hilmy; Ah. Zakki Fuad (CV. Media Digital Publikasi Indonesia, 2026)
Numerous institutions, each with unique traits, power dynamics, and political stances, have contributed to the development of Islamic education in Indonesia. Qur'anic Learning Centers (Taman Pendidikan Al-Qur'an/TPQ), Islamic Elementary Schools (Madrasah Diniyah/Madin), Pesantren, Madrasah, and Islamic Higher Education Institutions (Perguruan Tinggi Agama Islam/PTAI) are the five categories of Islamic educational institutions in which this study seeks to characterize the politics of education and institutional differentiation. This study investigates how differences in institutional structures are created by political configurations and how they, in turn, affect the quality and accessibility of Islamic education through a methodical literature review of laws, regulations, and socio-political dynamics. The results show that, in terms of institutional standing, societal legitimacy, state regulation, curriculum autonomy, and finance sources, the five institutions hold distinct positions along a continuum. Madin and TPQ have a great deal of autonomy but little assistance from the government. Pesantren's dual model (salafiyah–khalafiyah) places them in an intermediate position. In the meantime, Madrasah and PTAI are subject to more stringent regulations and are completely integrated into the national education system. Decentralization, bureaucratization, and digital transformation exacerbate the problems of resource inequality and quality discrepancies among institutions. The concept of differentiated governance within Islamic education, the identification of a bureaucratization paradox that may limit institutional innovation, and a mapping of state-civil society organizational relations that is specifically embedded in the Indonesian Islamic education context are the three main theoretical contributions made by this study. To improve the standard and equity of Islamic education, the report suggests more flexible, inclusive, and cooperative policies engaging local communities, civil society organizations, and the government.